Grenzgänger . Freedom, Bright Spark - aka Out of Time - Schnabel, Pavel (Germany, 1999)
Soros Documentary Fund The film follows three lives shaped by the Cold War. A rock musician from Leipzig expatriated from East to West. A Vienna intellectual who crosses the Wall from the West to East. A dissident jailed in Prague. The rock musician failed in the West. The Viennese became a professor at Karl Marx University, Leipzig, East Germany. The Prague dissident scraped by as an unskilled labourer in a waterworks. Thomas "The Monster" Schoppe, ex-singer of the Renft Combo, seeks his comeback in the East after the fall of the Wall. Prof. Dr. Peter Porsch from Vienna has become the PDS whip in the legislature of Saxony, now part of West Germany. Ivan Dejmal in Prague has lived through four years in jail and twenty years of persecution. Three portraits following the trajectory of European post-war history - before and after the collapse of the Iron Curtain.